Herpes Simplex Virus 1 Induces Microglia Gasdermin D-Dependent Pyroptosis Through Activating the NLR Family Pyrin Domain Containing 3 Inflammasome - Hu, Xiao; Zeng, Qiongzhen; Xiao, Ji; Qin, Shurong; Wang, Yuan; Shan, Tianhao; Hu, Di; Zhu, Yexuan; Liu, Kaisheng; Zheng, Kai; Wang, Yifei; Ren, Zhe (Frontiers in Microbiology, 2022)
Herpes simplex virus type 1 (HSV-1) is a highly prevalent virus in humans and causes severe forms of inflammation, such as herpes simplex encephalitis (HSE). Pyroptosis is a new inflammatory cell death triggered by inflammasome and cysteine-requiring aspartate protease-1 (caspase-1) activation. Nonetheless, HSV-1 induces encephalitis, and cell death mechanisms are not understood. In this study, we confirmed for the first time that the DNA virus HSV-1 triggers Gasdermin D-dependent pyroptosis by activating NLR family pyrin domain containing 3 (NLRP3) inflammasomes in mouse microglia, leading to mature IL-1β production and active caspase-1 (p10) release. Inhibition of microglial NLRP3 inflammasome activation suppressed HSV-1-induced Gasdermin D-dependent pyroptosis. In addition, NLRP3 and IL-1β expression levels were significantly increased in the mouse model of herpes simplex encephalitis compared with normal mice without viral infection. Collectively, our data revealed that the activation of inflammasomes and GSDMD-dependent pyroptosis is the mechanism of HSV-1 inducing inflammation and provides treatment targets for viral inflammation.